Pengaruh Konflik Peran, Ketidakjelasan Peran, Struktur Audit, Motivasi Dan Kepuasan Kerja Pada Kinerja Auditor - Winidiantari, Putu Nita; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2015)
Auditor performance concern users of financial statements in its duty to audit and ensure that the financial statements have been prepared in accordance with generally acceptable accounting principles. This study aims to influence of role conflict, role ambiguity, audit structure, motivation, job satisfaction on performance auditor in KAP in Bali. The samples used  60 samples. The method of data was a questionnaire. Analysis techniques used  multiple linear regression analysis. The results describe the role conflict and role ambiguity does not have effect on the performance auditors. Other variables that audit structure, motivation, job satisfaction had positive impact in performance auditors.
Keywords: auditor, performance, role conflict, audit structure, motivation, role ambiguity, job satisfaction